Energy Utilization Index and Benchmarking for a Government Hospital - Thongkaw, Sirinath; Assawamartbunlue, Kriengkrai (Agriculture and Natural Resources, 2012)
The energy utilization index is a measure that can be used to identify whether energy is being efficiently used. Energy consumption in public buildings is extremely large and is difficult to control and monitor. An efficient index based on engineering principles and ease of use was developed to monitor the energy usage in a public building,—a hospital—as a prototype building. The index was calculated as the difference between the actual energy consumption and optimal energy consumption expressed as a ratio of the optimal energy consumption. Actual energy consumption was defined as the amount indicated on an energy invoice. Optimal energy consumption was derived based on several engineering standards and codes as a function of variables such as the number of officers, number of customers, operating hours and building areas, among other factors. The ‘EnergyPlus’ simulation program was used to analyze optimal energy consumption. Based on the results, the prototype hospital could save up to 15% on energy consumption if the building were improved to comply with standards and codes.